Housing, Class Politics, and State Power: The Making of Urban Space in Karachi - Amjad, Risham (Tufts University Tisch Library, 2025)
Thesis (M.A.)--Tufts University, 2025.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Kristin Skrabut.; Committee: Hassaan Khan.; Keywords: Urban planning, and Public policy